Implementasi Program Penyediaan dan Pengembangan Sarana dan Prasarana Pertanian di Desa Sukodadi Kecamatan Sukodadi Kabupaten Lamongan - Salsa Izza Shafinaz Sukardi; Tauran Tauran; Tjitjik Rahaju; Indah Prabawati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
The agricultural sector is a vital pillar in maintaining food security and enhancing the livelihoods of rural communities. In an effort to improve agricultural productivity, the Government of Lamongan Regency, through the Food Security and Agriculture Agency (DKPP), has implemented the Agricultural Facilities and Infrastructure Provision and Development Program. This program is designed to strengthen agricultural production capacity by supporting the availability of farming machinery, improving irrigation networks, and developing farm access roads. Despite its strategic importance, the program’s implementation continues to encounter various obstacles, including constrained budget availability, unequal distribution of agricultural facilities, reliance on rain-fed irrigation systems, substandard farm road infrastructure, and limited intensity of agricultural extension services. This research aims to examine the implementation of the Agricultural Facilities and Infrastructure Provision and Development Program in Sukodadi Village, Sukodadi District, Lamongan Regency. The study adopts a qualitative descriptive approach, utilizing data collected through in-depth interviews, direct field observations, and document review. Analysis is conducted using the Van Meter and Van Horn policy implementation framework, which emphasizes six key variables: policy standards and objectives, resource adequacy, characteristics of implementing organizations, inter-organizational communication, implementer disposition, and social, economic, and political conditions. The results reveal that although policy standards and objectives are well defined, program execution remains suboptimal due to limited resources and insufficient institutional support at the operational level. Consequently, stronger coordination among implementing actors and improved resource optimization are necessary to achieve more effective and sustainable agricultural development outcomes.